Administration of the D-A structure and steric hindrance effect to construct efficient red emitters for high-performance OLEDs with low efficiency roll-off. (August 2021) - Ding, Guan-Yu; Zang, Chun-Xiu; Zhang, Han; Su, Zhong-Min; Li, Guang-Fu; Wen, Li-Li; Han, Xu; Xie, Wen-Fa; Shan, Guo-Gang
Abstract: Restricted by the energy-gap law and π-π stacking, developing highly efficient red emitting materials and corresponding organic light-emitting diodes (OLEDs) having the emission over 600 nm is a formidable challenge. Three red emitters, namely DPABz-TPA, 2DPABz-TPA, and 3DPABz-TPA, are developed bearing mono-, bis-, and tri-[2, 1, 3]benzothiadiazole (Bz) substituted triphenylamine (TPA) as the emissive core and bulky diphenylamine (DPA) as the steric protection units. All compounds display strong red emission with peaks at 645 nm and high efficiency up to 38%. Compared with reference molecule DPABz-TPA, both 2DPABz-TPA and 3DPABz-TPA exhibit higher radiative transition rate and thermal stability. The OLEDs based on 2DPABz-TPA and 3DPABz-TPA thus show superior EL efficiencies of the maximum current efficiency of 2.5 and 2.4 cd A −1, and external quantum efficiency of 2.9% and 3.2% compared with those of DPABz-TPA (1.9 cd A −1 and 2.1%). More importantly, the efficiency roll-off of OLED based on sterically protected 3DPABz-TPA obviously decreases owing to limited intermolecular packing. These results indicate that the strategy combined multiple donor-acceptor units and steric hindrance effect is favorable for constructing robust red emitters for efficient OLEDs. Highlights: The multiple D-A moieties and steric hindrance are combined to design red materials. All devices based on designed compounds show red emission with peaks at 635 nm. 2DPABz-TPA and 3DPABz-TPA exhibit improved EL efficiencies compared with DPABz-TPA. 3DPABz-TPA -based device exhibits suppressed efficiency roll-off.